2005
DOI: 10.1007/bf03215243
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Tunability in Au−VO2 Thermochromic Nano-composites

Abstract: A new type of photo-active nano-composite material appropriate for Ultra-fast Nonlinear Optical (3) ( ) applications has been synthesized and optically characterized. Compared to standard noble metal particles-oxide nano-composites exhibiting a superior effective (3) ( ) due to the enhancement of the local electric field, these Au-VO 2 nano-composites display an additional reversibly tunable surface plasmon frequency under external temperature stimuli. Such a smart plasmon tunability is correlated to the Mott'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 52 publications
5
40
0
2
Order By: Relevance
“…In the early stages, the film showed that as the grain size increased, the SMT decreased, but hysteresis continued to increase. The changes of the thermo-optical properties of VO 2 thin films are usually explained as results of the competing effects between grains size, nucleation defects, grain boundaries and crystal imperfections [32,33]. Therefore the differences in the morphologies and crystal orientations of the films lead to the distinctive SMT characteristics seen in the curves of Figs 3b but not only because of the variation in crystal grain sizes.…”
Section: Resultsmentioning
confidence: 99%
“…In the early stages, the film showed that as the grain size increased, the SMT decreased, but hysteresis continued to increase. The changes of the thermo-optical properties of VO 2 thin films are usually explained as results of the competing effects between grains size, nucleation defects, grain boundaries and crystal imperfections [32,33]. Therefore the differences in the morphologies and crystal orientations of the films lead to the distinctive SMT characteristics seen in the curves of Figs 3b but not only because of the variation in crystal grain sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Since the surface plasmon resonance wavelength (λ SPR ) depends on their particle size, shape, inter-particle distance and the dielectric function of the surrounding host [9][10][11][12][13], the tunable λ SPR in the visible and near infrared regions has been achieved by changing these parameters of the metallic nanoparticles [9][10][11][12][13][14]. Recently, a great interest has been made to tune λ SPR of noble metal nanoparticles by using dielectric functional materials such as thermochromic [15][16][17][18], electrochromic [19] or photochromic [20], as the matrices. The use of dielectric functional materials as the matrices opens a range of possibilities for tuning the λ SPR in a controllable manner.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dielectric functional materials as the matrices opens a range of possibilities for tuning the λ SPR in a controllable manner. Recently, the effect of external temperature stimuli on the plasmon resonance of Au or Ag nanoparticles embedded in a thermochromic VO 2 matrix, of composite Au-VO 2 [17,18] or Au-on-VO 2 core shell particles [8,21] or Ag on top of VO 2 [15] has been sparsely explored with only few reports. It is well-known that VO 2 undergoes a reversible first-order phase transition from semiconductor to metal at critical temperature Tc = 68 o C, accompanied by large change in optical properties in the infrared region [22][23][24] which will be exploited to modulate the λ SPR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, this can enable the measurement of nanoscale heat transfer through the investigation of such phase transformations [1]. On the other hand, this could be used to modify the global medium optical properties [7]. This effect has been supposed to be at the origin of the optical limitation phenomenon in colloidal solutions (induced light scattering by formation of gas bubbles around gold colloids) [8,9].…”
Section: Introductionmentioning
confidence: 99%